Debating archaeology - Binford, Lewis R. (Lewis Roberts), 1931-2011 (Studies in archaeology., 2009)
In this volume, the founder of processual archaeology, Lewis R. Binford collects and comments on the twenty-eight substantive papers published in the 1980's, the third in his set of collected papers. A 2009 Foreword allows for further reflections on this work.